(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In article actual problems of Islam and others religious a current in modern Kazakhstan are considered. Today the religion is the integral element of society which keeps and strengthens the state. In this article history of formation and development of Islam in Kazakhstan is briefly stated. Also in article the analysis on religious situation in the state and on policy of the state in religious institutes is given. In general, in article, relying on actual researches the statement is given that religious situation in Kazakhstan develops by the principle of tolerance and mutual understanding. Key words: Republic of Kazakhstan, religion Islam, Orthodoxy, tolerance, interfaith consent.